ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI UPAYA PENCEGAHAN PENYAKIT JANTUNG KORONER (PJK) DI DESA PANDES TASIKMADU KARANGNYAR - Diyono Diyono; Nisma Ayu Ambarwati (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2017)
Coronary Heart Disease (CHD) is still the leading cause of death in Indonesia. The bestmanagement of CHD is primary prevention, but not many people who do well with a widevariety of factors that influence. Objective: (1) know the description of prevention ofcoronary heart disease (2) Analyze the factors that affect the prevention of coronary heartdisease, including age, education level, and the level of knowledge of the CHD disease.Method: analytical research correlational. Subjects 65 people in the village PandesTasikamadu Karanganyar. Samples taken purposive sampling. Data were analyzed withMultiple Linear Regression Test using SPSS 18.Results: (1) In general, respondents are already doing prevention of coronary heartdisease as well with an average value of 22.85. (2) Age (p = 0.474) and educational level(p = 498) did not significantly influence the prevention of coronary heart disease (3) Thelevel of knowledge and perception of coronary heart disease significantly influence theprevention of coronary heart disease (4) perceptions of coronary heart disease is themost influential factor towards the prevention of coronary heart disease (p = 0.001; β =0.665). Conclusions: factors that influence the prevention of coronary heart disease is thelevel of knowledge (p = 0.015) and perception (p = 0.001).Keywords: Coronary Heart Disease, Age, Education Level, Knowledge